Observation of the changes in circulatory system and dermatological state in patients with localized scleroderma - Bergler-Czop, Beata; Dukalska, Maria; Rokicki, Władysław; Markiewicz-Łoskot, Grażyna; Lis, Anna; Bilewicz-Wyrozumska, Teresa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
The circulatory system was studied in 29 patients with diagnosis of localized scleroderma (at the age of 12 up to 28 years, mean age was 18,1 years ±3,9), 18 females and 11 males. In Department of Pediatric Cardiology were performed: physical examination standard electrocardiogram (ECG), 24-hour Holter ECG monitoring, a treadmill exercise test conducted according to Bruce protocol as well as echocardiography plus Doppler’s effect investigation. In Department of Dermatology dermatological state was examined by physical exam, and its changes – by interview, photos and hospital and ambulatory documents. Radiological exams of the chest, palms and upper part of alimentary canal and serum exam (ANA – antinuclear antybodies) were also performed. Similarly as 10 years ago, during the routine electrocardiogram (ECG), the incomplete right branch block has been found in majority of patients. During 24-hour Holter ECG monitoring, in 75% of cases regular records were stated while in 25% of patients not several supraventricular arrhythmia was found. Echocardiographic abnormalities (valvular regurgitation) were found in 2 cases. During the exercise tests in 2 patients dysrrhythmia has been challenged. Dermatological investigations revealed the improvement of the local state in over 13% of patients. Aggravation was observed in 44.8% of patients. No radiological changes were observed. In 13.8% of cases ANA were disclosed. Results of cardiological investigation appeared not to point at any progression of changes in the circulatory system in a group under examination during the last 10 years. On the other hand dermatological investigation often suggests aggravation or no changes in time. Is it thought that there is no correlation between dermatological and cardiological changes in patients with localized scleroderma.